Full characterization of the three pathways of the complement system in patients with systemic lupus erythematosus - García-González, María; Gómez-Bernal, Fuensanta; Quevedo-Abeledo, Juan C.; Fernández-Cladera, Yolanda; González-Rivero, Agustín F.; de Vera-González, Antonia; de la Rua-Figueroa, Iñigo; López-Mejias, Raquel; Díaz-González, Federico; González-Gay, Miguel Á.; Ferraz-Amaro, Iván (Frontiers in Immunology, 2023)
Background To date a complete characterization of the components of the complement (C) pathways (CLassical, LEctin and ALternative) in patients with systemic lupus erythematosus (SLE) has not been performed. We aimed to assess the function of these three C cascades through functional assays and the measurement of individual C proteins. We then studied how they relate to clinical characteristics. Methods New generation functional assays of the three pathways of the C system were assessed in 284 patients with SLE. Linear regression analysis was performed to study the relationship between the activity, severity, and damage of the disease and C system. Results Lower values of the functional tests AL and LE were more frequent than those of the CL pathway. Clinical activity was not related to inferior values of C routes functional assays. The presence of increased DNA binding was negatively linked to all three C pathways and products, except for C1-inh and C3a which were positively related. Disease damage revealed a consistent positive, rather than a negative, relationship with pathways and C elements. Anti-ribosomes and anti-nucleosomes were the autoantibodies that showed a greater relationship with C activation, mainly due to the LE and CL pathways. Regarding antiphospholipid antibodies, the most related with C activation were IgG anti-β2GP, predominantly involving the AL pathway. Conclusion Not only the CL route, but also the AL and LE are related to SLE features. C expression patterns are linked to disease profiles. While accrual damage was associated with higher functional tests of C pathways, anti-DNA, anti-ribosomes and anti-nucleosomes antibodies, were the ones that showed a higher relationship with C activation, mainly due to the LE and CL pathways.